Pengaruh Manajemen Sumber Daya Pendidikan Terhadap Prestasi Siswa Madrasah Aliyah Negeri Di Sulawesi Selatan - Abd. Wahid Tahir; Andi Bunyamin (Universitas Muslim Indonesia, 2023)
This study focuses on the influence of educational resource management on student achievement at the State Aliyah Madrasa in South Sulawesi, which aims to analyze the Effect of Educational Resource Management on Student Achievement at the State Aliyah Madrasa in South Sulawesi. This study uses a quantitative approach to the type of research that will be used is type of survey research. Where survey, is a study that takes samples from one population and uses data instruments in the form of questionnaires, interviews, observations, and document data as a means of collecting basic data. The approach in this study uses a positivistic approach. The population in this study were all teachers at Aliyah madrasas in South Sulawesi. The sample taken from this population is 150 teachers. Of the five madrasas in South Sulawesi. With descriptive statistical analysis techniques, and inferential statistical analysis techniques. The results showed that first, the implementation of management of educational resources in the State Madrasah Aliyah in South Sulawesi was in a good category with a total percentage of 57%, second, the student achievement of the State Madrasah Aliyah in South Sulawesi was in the very good category with a percentage of 69%, third, and the results of the regression calculations show that there is an influence of management of content standards, process standards, educator and educational staff standards, facilities, and infrastructure standards, education financing standards, on student achievement at State Madrasah Aliyah in Sulawesi-South. Novelty, The role of educational resource management at the State Aliyah Madrasa in South Sulawesi, in improving student achievement to create high-quality Aliyah madrasa students who are ready to compete in the era of the industrial revolution 4.0.